Highly Selective Catalytic Dechlorination of Dichloromethane to Chloromethane over Al−Ti Mixed Oxide Catalysts. Issue 20 (31st August 2020) - Yoon, Wongeun; Lee, Seungjun; Noh, Yuseong; Park, Seongmin; Kim, Youngmin; Ju Kim, Hyung; Chae, Ho‐Jeong; Bae Kim, Won
Abstract: In this paper, a series of Al−Ti mixed oxides with different Al/Ti ratios are prepared by a simple sol‐gel method and they are used as active catalysts for selective dechlorination of dichloromethane to chloromethane. The Al−Ti mixed oxide catalyst with the same molar ratio of Al and Ti shows the highest activity in dechlorination of dichloromethane. The strong and abundant Lewis acid sites in the Al−Ti mixed oxides formed along with Al−O−Ti bondings are responsible for the high catalytic activity toward the selective dechlorination reaction in this work. From a kinetic study, the activation energy of this reaction over the optimum Al−Ti mixed oxide catalyst appears to be 59.4 kJ mol −1 based on Langmuir‐Hinshelwood model. The improved catalytic performance suggests that the Al−Ti mixed oxide could be used as the effective catalyst for the highly selective dechlorination of dichloromethane to chloromethane. Abstract : Heterogeneous catalysis : The Al−Ti mixed oxide showed higher catalytic activity in novel selective dechlorination to convert dichloromethane into value‐added intermediates. The increased amount and strength of acid sites enhanced by formations of Al−O−Ti bonds in the Al−Ti mixed oxide could lead to the improved turnover frequency of catalyst.